COFs flame-retardant polyethylene composite material for rotational molding and preparation method of COFs flame-retardant polyethylene composite material

By introducing flame retardant covalent organic frame materials and copper chelates into rotomolded polyethylene and combining carbon nanotubes, the problem of insufficient flame retardant performance of traditional rotomolded polyethylene products is solved, achieving efficient flame retardant effect and environmental protection characteristic.

CN119220003AActive Publication Date: 2024-12-31CIXI AIDIWEI ROTOMOLDING EQUIP TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411419039.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-31
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

Traditional rotomolded polyethylene products have insufficient flame retardant and antistatic properties, which limits their application in special fields. Moreover, the large amount of traditional flame retardant added leads to a degradation of performance, making them not suitable for rotomolding processing.

Method used

Using flame retardant covalent organic frame (COFs) materials, the Cu@COFs-COOH powder is formed by introducing flame retardant elements such as imides and copper chelates into the COFs structure, combining carbon nanotubes and other toughening agents. Improve the flame retardant properties of the material.

Benefits of technology

It realizes effective isolation of oxygen at high temperatures, slows down combustion rate, improves the thermal stability and flame retardant properties of the material, and is non-toxic and more environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220003A_ABST
    Figure CN119220003A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer composite materials, and relates to a COFs flame-retardant polyethylene composite material for rotational moulding and a preparation method thereof, the composite material comprises the following components: 15.0%-35.0% of linear low density polyethylene, 35.0%-55.0% of low density polyethylene, and flame-retardant master batch; the flame-retardant master batch comprises the following components in percentage by weight: 10.0%-35.0% of linear low-density polyethylene, 0%-10.0% of a carbon nano tube, 1.0%-12.0% of Cu (at) COFs-COOH, 1.0%-10.0% of a toughening agent, 1.0%-10.0% of polyethylene wax and 1.0%-10.0% of an antioxidant. Wherein the proportion is mass percent. The composite material disclosed by the invention can isolate oxygen, reduce surface temperature, reduce heat release and form a porous foam carbon layer under a high-temperature condition, so that the flame-retardant effect is remarkably improved, and compared with a traditional halogen flame retardant, no toxic gas is generated, and the composite material is more environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials and relates to a COFs flame-retardant polyethylene composite material for rotational molding and a preparation method thereof. Background Art

[0002] Rotomolding, also known as rotational molding or rotational molding, is a molding process for producing hollow plastic products without pressure. It is mainly used to produce large, seamless products with uniform wall thickness, and is particularly suitable for manufacturing durable and complex hollow plastic products. Therefore, it has become one of the important branches of the plastics processing field. Rotomolded products are widely used in many fields, including agriculture (such as large water tanks), military (such as packaging boxes for missiles, rockets, and mines), the automotive industry (such as durable vehicle parts), and the toy industry (such as delicate and safe plastic products). The shortcomings of traditional rotomolded polyethylene products in flame retardancy and antistatic properties have greatly limited the application of their products in special fields (such as electronic and electrical packaging, fuel and chemical storage and transportation, etc.). On the other hand, traditional polyolefin flame retardant methods are not suitable for rotomolding processing due to the large amount of flame retardant added and the significant decline in product performance, and cannot be used in the production of rotomolded products. Therefore, rotomolded polyethylene needs to be flame retardant modified to improve its properties.

[0003] Flame-retardant covalent organic framework (COFs) materials are an important development direction. The main approach is to improve the flame retardant properties by introducing flame retardant elements or functional groups into the COFs structure. For example, imide COF with rearrangement characteristics releases CO2 during the heat-induced structural rearrangement process, thereby exhibiting good flame retardant properties (eScience2(2022)311-318). In addition, COF-based phosphorus, nitrogen and silicon synergistic flame retardants (PA-COF@MT) were synthesized by phytic acid (PA), montmorillonite (MT) and covalent organic framework (COF), showing excellent flame retardant effects in epoxy resins. In recent years, transition metal compounds (such as copper, cobalt, nickel, etc.) have begun to be studied and applied more and more widely as flame retardants. Among them, copper chelates have similar aromatic ring structures. Metallic copper will catalyze carbonization during the combustion of the polymer to form a denser and tougher carbon layer, which helps protect the material from further erosion by the flame. At the same time, copper chelates can improve the thermal stability of polymers, making the material stable at higher temperatures and less prone to combustion, giving it unique advantages in practical applications. Summary of the Invention

[0004] In order to solve the above technical problems existing in the prior art, the present invention proposes a COFs flame-retardant polyethylene composite material for rotational molding and a preparation method thereof, and its specific technical solution is as follows:

[0005] A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding comprises the following steps:

[0006] Step (1) COFs preparation, specifically comprising:

[0007] Step 1: A certain amount of 1,3,5-tri-p-formylphenylbenzene was dissolved in DMAc, and then dioxane and a certain amount of 3,5-diamino-1,2,4-triazole were added to obtain a light yellow solution. An acetic acid aqueous solution was added to obtain a COF mother liquor. The obtained COF mother liquor was then introduced into a polytetrafluoroethylene-lined autoclave and heated at 60-150°C for 24-96 hours. The obtained COF powder was then washed several times with methanol, acetone and tetrahydrofuran, and dried in room air to obtain a COFs powder having the structural formula shown in Formula (I):

[0008]

[0009] Step 2: Weigh a certain amount of COFs powder of structural formula (I) and add a certain amount of acetone solution of succinic acid. Heat the reaction mixture at 40-100°C for 12-36 hours, collect the precipitate by centrifugation, and wash it with acetone. The resulting powder is dried under vacuum overnight to obtain COFs-COOH powder with the structural formula shown in formula (II):

[0010]

[0011] Furthermore, the reaction mixture is heated at 40-100° C. for 12-36 hours, with the optimal reaction temperature being 90° C. and the reaction time being 24 hours.

[0012] Step 3: Under ultrasonic conditions, the COFs-COOH powder is dispersed in a mixed solution of water and acetone, and a certain amount of copper sulfate solution is added. The stirring time is 2 to 10 hours, and the mixture is filtered and washed to obtain Cu@COFs-COOH powder. The structural formula is as follows:

[0013]

[0014]

[0015] Furthermore, the COFs-COOH powder is dispersed in a mixed solution of water and acetone, and then a certain amount of copper sulfate solution is added, and the stirring time is 2 to 10 hours, and the optimal stirring time is 5 hours.

[0016] Step (2) Masterbatch preparation:

[0017] Cu@COFs-COOH powder and PE wax are weighed according to the weight ratio and added into a high-speed mixer, the blending temperature is 85-110°C, and the blending time is 5-8 minutes; then LLDPE, carbon nanotubes CNT, toughening agent and antioxidant are added and blended at 85-110°C for 3-5 minutes; the above mixed materials are put into a twin-screw extruder for extrusion at an extrusion temperature of 195°C, and then cooled, pelletized and dried to obtain flame retardant masterbatch.

[0018] Furthermore, the PE wax in the flame retardant masterbatch is one of PEW-032, PEW-031, PEW-030 or a combination thereof.

[0019] Furthermore, the linear low-density polyethylene (LLDPE) in the flame-retardant masterbatch is one of LLDPE-7050, LLDPE-9020, and LLDPE-9085, or a combination thereof.

[0020] Furthermore, the carbon nanotubes CNT in the flame retardant masterbatch are single-walled carbon nanotubes or multi-walled carbon nanotubes One or a combination of .

[0021] Furthermore, the toughening agent in the flame retardant masterbatch is one of POE-g-MAH, POE-g-GMA, PE-g-MAH or a combination thereof.

[0022] Furthermore, the antioxidant in the flame retardant masterbatch is one of BHT, AO-1010, AO-1076, AO-3114, AO-330 or a combination thereof.

[0023] Furthermore, the Cu@COFs-COOH powder and PE wax are added to a high-speed mixer, the blending temperature is 85-110° C., the blending time is 5-8 min, the optimal blending temperature is 90° C., and the blending time is 8 min.

[0024] Furthermore, the LLDPE, carbon nanotubes CNT, toughening agent and antioxidant are added and blended at 85-110° C. for 3-5 minutes, the optimal blending temperature is 90° C., and the blending time is 4 minutes.

[0025] Step (3) extrusion granulation:

[0026] LLDPE, LDPE, and Cu@COFs-COOH masterbatch were weighed according to the weight ratio, blended in a high-speed mixer at 85-110° C. for 10-20 min, and then put into a twin-screw extruder for extrusion (temperature 195° C.), cooled, pelletized, and the obtained particles were dried for use.

[0027] Furthermore, the low-density polyethylene (LDPE) is one of DFDA-7042, DFDB-7042, and DFDC-7042, or a combination thereof, and the linear low-density polyethylene (LLDPE) is one of LLDPE-7050, LLDPE-9020, and LLDPE-9085, or a combination thereof.

[0028] Furthermore, the LLDPE, LDPE and Cu@COFs-COOH powders are added to a high-speed mixer, the blending temperature is 85-110° C., the blending time is 10-20 min, the optimal blending temperature is 90° C., and the blending time is 15 min.

[0029] Step (4) mechanical grinding:

[0030] Under the protection of nitrogen, the particles obtained in step (3) are ground into powder of about 40 to 50 meshes using a grinder to obtain a COFs flame-retardant polyethylene composite material for rotational molding.

[0031] A COFs flame-retardant polyethylene composite material for rotational molding, specifically comprising the following components:

[0032] LLDPE 15.0%~35.0%,

[0033] LDPE 35.0%~55.0%,

[0034] Flame retardant masterbatch;

[0035] Wherein, the flame retardant masterbatch includes the following components:

[0036] LLDPE 10.0%~35.0%,

[0037] CNT 0%~10.0%,

[0038] Cu@COFs-COOH 1.0%~12.0%,

[0039] Toughening agent 1.0% to 10.0%,

[0040] PE wax 1.0%~10.0%,

[0041] Antioxidant 1.0% to 10.0%,

[0042] The proportions are all in mass percentage.

[0043] Compared with the prior art, the advantages of the present invention are:

[0044] First, the Cu@COFs-COOH powder provided by the present invention is rich in imine bonds (-CH=N-) or other nitrogen-containing functional groups. Under high temperature conditions, it can release non-combustible gases such as nitrogen, water vapor, and ammonia. The generated non-combustible gases adhere to the surface of the polymer, isolating oxygen and preventing combustion, thereby achieving a flame retardant effect. At the same time, thermal decomposition also removes a large amount of heat, lowering the surface temperature, making it difficult to burn, or even terminating combustion. At the same time, the carboxylic acid groups in the COF can act as a dehydrating agent. During the esterification reaction and melting process, the non-combustible gases produced cause the molten system to expand and foam, forming inorganic matter and carbon residues, which further foam and ultimately form a porous foam carbon layer.

[0045] 2. In the Cu@COFs-COOH powder provided by the present invention, the carboxylic acid group (-COOH) has a relatively rich copper chelating active site, which promotes the formation of coordination bonds. This allows the copper chelate to promote the formation of a carbon layer during the combustion process to isolate oxygen and heat, slow down the combustion rate and heat release rate of the polyethylene material, reduce the release of heat, and improve the flame retardant effect of the material. The copper chelate has good chemical stability and is not easy to decompose in the environment. It can improve the thermal stability of the polymer, making it more difficult to decompose at high temperatures, thereby improving the flame retardant properties. On the other hand, compared with some traditional halogen flame retardants, no toxic gas is generated, which is more environmentally friendly.

[0046] Third, traditional intumescent flame retardants require a three-component compounding, which has disadvantages such as large addition amounts, poor compatibility, easy migration, and reduced flame retardant effect. Furthermore, the ratio is difficult to control and has a significant impact on the mechanical properties of the polymer. In contrast, the Cu@COFs-COOH powder structure provided by the present invention, the imine bond (-CH=N-) or other nitrogen-containing functional groups on the COF ring, the carboxylic acid, and the chelated copper element produce a synergistic effect during the polyethylene combustion process, significantly enhancing the flame retardant effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Schematic diagram of COFs-COOH powder obtained during the COFs preparation process of this embodiment. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solution and technical effect of the present invention more clear, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0049] The embodiment of the present invention discloses a COFs flame-retardant polyethylene composite material for rotational molding, comprising the following components:

[0050] LLDPE 15.0%~35.0%,

[0051] LDPE 35.0%~55.0%,

[0052] Flame retardant masterbatch;

[0053] Wherein, the flame retardant masterbatch includes the following components:

[0054] LLDPE 10.0%~35.0%,

[0055] CNT 0%~10.0%,

[0056] Cu@COFs-COOH 1.0%~12.0%,

[0057] Toughening agent 1.0% to 10.0%,

[0058] PE wax 1.0%~10.0%,

[0059] Antioxidant 1.0% to 10.0%,

[0060] The proportions are all in mass percentage.

[0061] Example 1:

[0062] A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding comprises the following steps:

[0063] Step (1) COFs preparation:

[0064] Step 1: A certain amount of 1,3,5-tri-p-formylphenylbenzene was dissolved in DMAc, and then dioxane and a certain amount of 3,5-diamino-1,2,4-triazole were added to obtain a light yellow solution. An acetic acid aqueous solution was then added, and the obtained solution, i.e., the COF mother liquor, was introduced into a polytetrafluoroethylene-lined autoclave and heated at 90°C for 48 hours. The obtained COF powder was then washed several times with methanol, acetone, and tetrahydrofuran, and dried in room air to obtain COFs powder, the structural formula of which is shown in Formula (I):

[0065]

[0066]

[0067] Step 2: Weigh a certain amount of (I)COFs powder and add a certain amount of acetone solution of succinic acid. Heat the reaction mixture at 90°C for 24 hours, collect the precipitate by centrifugation, wash with acetone, and dry the obtained powder under vacuum overnight to obtain Figure 1 The COFs-COOH powder shown has a structural formula as shown in formula (II):

[0068]

[0069] Step 3: Under ultrasonic conditions, the COFs-COOH powder is dispersed in a mixed solution of water and acetone, and then a certain amount of copper sulfate solution is added. The mixture is stirred for 5 hours, filtered, and washed to obtain Cu@COFs-COOH powder, the structural formula of which is shown in Formula (III):

[0070]

[0071]

[0072] Step (2) Masterbatch preparation:

[0073] 9 parts of Cu@COFs-COOH powder and 2 parts of PE wax PEW-031 were weighed and added to a high-speed mixer at a blending temperature of 90°C for 8 minutes; then 15 parts of LLDPE DFDA-7042, 2 parts of toughening agent POE-g-MAH, and 2 parts of antioxidant AO-1010 were added and blended at about 90°C for 4 minutes; the above mixed materials were put into a twin-screw extruder and extruded at an extrusion temperature of 195°C, then cooled, pelletized, and dried to obtain flame retardant masterbatch.

[0074] Step (3) extrusion granulation:

[0075] LLDPE DFDB-7042, HDPE HDPE-7000F, and Cu@COFs-COOH masterbatch were weighed according to the weight ratio, blended in a high-speed mixer at 90°C for 15 minutes, and then put into a twin-screw extruder for extrusion at an extrusion temperature of 195°C. The mixture was then cooled and pelletized, and the obtained particles were dried for use.

[0076] Step (4) mechanical grinding:

[0077] Under the protection of nitrogen, the particles obtained in step (3) are ground into powder of about 40 to 50 meshes using a grinder to obtain a COFs flame-retardant polyethylene composite material for rotational molding.

[0078] The testing devices used were: Instron 5567 (tensile properties, test standard: ASTM D638) produced by Instron Corporation of the United States; XJ-50Z (impact properties, Izod notched impact strength test standard: ASTM D256) produced by Chengde Dahua Company.

[0079] Example 2:

[0080] A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding comprises the following steps:

[0081] Step (1) COFs preparation method is the same as Example 1;

[0082] Step (2) Masterbatch preparation:

[0083] Weigh 8 parts of Cu@COFs-COOH powder and 2 parts of PE wax PEW-031 and add them into a high-speed mixer at a blending temperature of 90°C for 8 minutes; then add 15 parts of LLDPE DFDA-7042 and 1 part of carbon nanotubes. 2 parts of toughening agent POE-g-MAH and 2 parts of antioxidant AO-1010 are blended at about 90°C for 4 minutes; the above mixed materials are put into a twin-screw extruder for extrusion, cooling, pelletizing and drying to obtain flame retardant masterbatch;

[0084] Step (3) extrusion granulation method is the same as that in Example 1;

[0085] The mechanical grinding method in step (4) is the same as that in Example 1.

[0086] The testing devices used were: Instron 5567 (tensile properties, test standard: ASTM D638) produced by Instron Corporation of the United States; XJ-50Z (impact properties, Izod notched impact strength test standard: ASTM D256) produced by Chengde Dahua Company.

[0087] Example 3:

[0088] A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding comprises the following steps:

[0089] Step (1) COFs preparation method is the same as Example 1;

[0090] Step (2) Masterbatch preparation:

[0091] Weigh 7 parts of Cu@COFs-COOH powder and 2 parts of PE wax PEW-031 and add them into a high-speed mixer at a blending temperature of 90°C for 8 minutes; then add 15 parts of LLDPE DFDA-7042 and 2 parts of carbon nanotubes. 2 parts of toughening agent POE-g-MAH and 2 parts of antioxidant AO-1010 are blended at about 90°C for 4 minutes; the above mixed materials are put into a twin-screw extruder for extrusion, cooling, pelletizing and drying to obtain flame retardant masterbatch;

[0092] Step (3) extrusion granulation method is the same as that in Example 1;

[0093] The mechanical grinding method in step (4) is the same as that in Example 1.

[0094] The testing devices used were: Instron 5567 (tensile properties, test standard: ASTM D638) produced by Instron Corporation of the United States; XJ-50Z (impact properties, Izod notched impact strength test standard: ASTM D256) produced by Chengde Dahua Company.

[0095] Example 4:

[0096] A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding comprises the following steps:

[0097] Step (1) COFs preparation method is the same as Example 1;

[0098] Step (2) Masterbatch preparation:

[0099] Weigh 6 parts of Cu@COFs-COOH powder and 2 parts of PE wax PEW-031 and add them into a high-speed mixer at a blending temperature of 90°C for 8 minutes; then add 15 parts of LLDPE DFDA-7042 and 3 parts of carbon nanotubes. 2 parts of toughening agent POE-g-MAH and 2 parts of antioxidant AO-1010 are blended at about 90°C for 4 minutes; the above mixed materials are put into a twin-screw extruder for extrusion, cooling, pelletizing and drying to obtain flame retardant masterbatch;

[0100] Step (3) extrusion granulation method is the same as that in Example 1;

[0101] The mechanical grinding method in step (4) is the same as that in Example 1.

[0102] The testing devices used were: Instron 5567 (tensile properties, test standard: ASTM D638) produced by Instron Corporation of the United States; XJ-50Z (impact properties, Izod notched impact strength test standard: ASTM D256) produced by Chengde Dahua Company.

[0103] Example 5:

[0104] A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding comprises the following steps:

[0105] Step (1) COFs preparation method is the same as Example 1;

[0106] Step (2) Masterbatch preparation:

[0107] Weigh 4 parts of Cu@COFs-COOH powder and 2 parts of PE wax PEW-031 and add them into a high-speed mixer at a blending temperature of 90°C for 8 minutes; then add 15 parts of LLDPE DFDA-7042 and 4 parts of carbon nanotubes. 2 parts of toughening agent POE-g-MAH and 2 parts of antioxidant AO-1010 are blended at about 90°C for 4 minutes; the above mixed materials are put into a twin-screw extruder for extrusion, cooling, pelletizing and drying to obtain flame retardant masterbatch;

[0108] Step (3) extrusion granulation method is the same as that in Example 1;

[0109] The mechanical grinding method in step (4) is the same as that in Example 1.

[0110] The testing devices used were: Instron 5567 (tensile properties, test standard: ASTM D638) produced by Instron Corporation of the United States; XJ-50Z (impact properties, Izod notched impact strength test standard: ASTM D256) produced by Chengde Dahua Company.

[0111] Example 6:

[0112] A COFs flame-retardant polyethylene composite material for rotational molding and a preparation method thereof, comprising the following steps:

[0113] Step (1) COFs preparation method is the same as Example 1;

[0114] Step (2) Masterbatch preparation:

[0115] Weigh 4 parts of Cu@COFs-COOH powder and 2 parts of PE wax PEW-031 and add them into a high-speed mixer at a blending temperature of 90°C for 8 minutes; then add 15 parts of LLDPE DFDA-7042 and 5 parts of carbon nanotubes. 2 parts of toughening agent POE-g-MAH and 2 parts of antioxidant AO-1010 are blended at about 90°C for 4 minutes; the above mixed materials are put into a twin-screw extruder for extrusion, cooling, pelletizing and drying to obtain flame retardant masterbatch;

[0116] Step (3) extrusion granulation method is the same as that in Example 1;

[0117] The mechanical grinding method in step (4) is the same as that in Example 1.

[0118] The testing devices used were: Instron 5567 (tensile properties, test standard: ASTM D638) produced by Instron Corporation of the United States; XJ-50Z (impact properties, Izod notched impact strength test standard: ASTM D256) produced by Chengde Dahua Company.

[0119] Example 7:

[0120] A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding comprises the following steps:

[0121] Step (1) COFs preparation method is the same as Example 1;

[0122] Step (2) Masterbatch preparation:

[0123] Weigh 3 parts of Cu@COFs-COOH powder and 2 parts of PE wax PEW-031 and add them into a high-speed mixer at a blending temperature of 90°C for 8 minutes; then add 15 parts of LLDPE DFDA-7042 and 6 parts of carbon nanotubes. 2 parts of toughening agent POE-g-MAH and 2 parts of antioxidant AO-1010 are blended at about 90°C for 4 minutes; the above mixed materials are put into a twin-screw extruder for extrusion, cooling, pelletizing and drying to obtain flame retardant masterbatch;

[0124] Step (3) extrusion granulation method is the same as that in Example 1;

[0125] The mechanical grinding method in step (4) is the same as that in Example 1.

[0126] The testing devices used were: Instron 5567 (tensile properties, test standard: ASTM D638) produced by Instron Corporation of the United States; XJ-50Z (impact properties, Izod notched impact strength test standard: ASTM D256) produced by Chengde Dahua Company.

[0127] Example 8:

[0128] A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding comprises the following steps:

[0129] Step (1) COFs preparation method is the same as Example 1;

[0130] Step (2) Masterbatch preparation:

[0131] Weigh 2 parts of Cu@COFs-COOH powder and 2 parts of PE wax PEW-031 and add them into a high-speed mixer at a blending temperature of 90°C for 8 minutes; then add 15 parts of LLDPE DFDA-7042 and 7 parts of carbon nanotubes. 2 parts of toughening agent POE-g-MAH and 2 parts of antioxidant AO-1010 are blended at about 90°C for 4 minutes; the above mixed materials are put into a twin-screw extruder for extrusion, cooling, pelletizing and drying to obtain flame retardant masterbatch;

[0132] Step (3) extrusion granulation method is the same as that in Example 1;

[0133] The mechanical grinding method in step (4) is the same as that in Example 1.

[0134] The testing devices used were: Instron 5567 (tensile properties, test standard: ASTM D638) produced by Instron Corporation of the United States; XJ-50Z (impact properties, Izod notched impact strength test standard: ASTM D256) produced by Chengde Dahua Company.

[0135] Example 9:

[0136] A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding comprises the following steps:

[0137] Step (1) COFs preparation method is the same as Example 1;

[0138] Step (2) Masterbatch preparation:

[0139] Weigh 1 part of Cu@COFs-COOH powder and 2 parts of PE wax PEW-031 and add them into a high-speed mixer at a blending temperature of 90°C for 8 minutes; then add 15 parts of LLDPE DFDA-7042 and 8 parts of carbon nanotubes. 2 parts of toughening agent POE-g-MAH and 2 parts of antioxidant AO-1010 are blended at about 90°C for 4 minutes; the above mixed materials are put into a twin-screw extruder for extrusion, cooling, pelletizing and drying to obtain flame retardant masterbatch;

[0140] Step (3) extrusion granulation method is the same as that in Example 1;

[0141] The mechanical grinding method in step (4) is the same as that in Example 1.

[0142] The testing devices used were: Instron 5567 (tensile properties, test standard: ASTM D638) produced by Instron Corporation of the United States; XJ-50Z (impact properties, Izod notched impact strength test standard: ASTM D256) produced by Chengde Dahua Company.

[0143] Comparative Example 1:

[0144] A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding comprises the following steps:

[0145] Step (1) COFs preparation method is the same as Example 1;

[0146] Step (2) Masterbatch preparation:

[0147] Weigh 2 parts of PE wax PEW-031, 15 parts of LLDPE DFDA-7042, and 3 parts of carbon nanotubes 2 parts of toughening agent POE-g-MAH and 2 parts of antioxidant AO-1010 are blended at about 90°C for 4 minutes; the above mixed materials are put into a twin-screw extruder for extrusion, cooling, pelletizing and drying to obtain flame retardant masterbatch;

[0148] Step (3) extrusion granulation method is the same as that in Example 1;

[0149] The mechanical grinding method in step (4) is the same as that in Example 1.

[0150] The testing devices used were: Instron 5567 (tensile properties, test standard: ASTM D638) produced by Instron Corporation of the United States; XJ-50Z (impact properties, Izod notched impact strength test standard: ASTM D256) produced by Chengde Dahua Company.

[0151] The material proportions of the above embodiments and comparative examples are shown in Table 1 below:

[0152]

[0153]

[0154] Table 1

[0155] The performance comparison of the above embodiments and comparative examples is shown in Table 2 below:

[0156]

[0157] Table 2

[0158] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the implementation process of the present invention is described in detail above, it is still possible for those familiar with the art to modify the technical solutions described in the above examples or to replace some of the technical features therein with equivalents. Any modifications, equivalent replacements, etc. made within the spirit and principles of the present invention shall be included in the scope of protection of the present invention.

Claims

1. A method for preparing a COFs flame-retardant polyethylene composite material for rotational molding, characterized in that: The following steps are involved: Step (1) COFs preparation, specifically comprising: The first step: dissolving 1,3,5-tri-p-formylphenylbenzene in DMAc, then adding dioxane and 3,5-diamino-1,2,4-triazole to obtain a light yellow solution, adding acetic acid aqueous solution, and then introducing the obtained solution, i.e., COF mother liquor, into a polytetrafluoroethylene-lined autoclave, and heating at 60-150° C. for 24-96 hours. The obtained COF powder is then washed several times with methanol, acetone and tetrahydrofuran, and dried in room air to obtain COFs powder, the structural formula of which is shown in formula (I): Step 2: Weigh the COFs powder, add acetone solution of succinic acid, heat the reaction mixture at 40-100° C. for 12-36 hours, collect the precipitate by centrifugation, wash with acetone, and dry the obtained powder under vacuum overnight to obtain COFs-COOH powder, the structural formula of which is shown in formula (II): Step 3: Under ultrasonic conditions, the COFs-COOH powder is dispersed in a mixed solution of water and acetone, and then copper sulfate solution is added. The stirring time is 2 to 10 hours, and the mixture is filtered and washed to obtain Cu@COFs-COOH powder, the structural formula of which is as follows: Step (2) Masterbatch preparation: Cu@COFs-COOH powder and PE wax are weighed according to the weight ratio and added into a high-speed mixer, the blending temperature is 85-110°C, and the blending time is 5-8 minutes; then linear low-density polyethylene LLDPE, carbon nanotubes CNT, toughening agent, and antioxidant are added and blended at 85-110°C for 3-5 minutes; the above mixed materials are put into a twin-screw extruder for extrusion, and then cooled, pelletized, and dried to obtain a flame retardant masterbatch; Step (3) extrusion granulation: Weigh linear low-density polyethylene LLDPE, low-density polyethylene LDPE, and flame-retardant masterbatch according to the weight ratio, blend them in a high-speed mixer at 85-110° C. for 10-20 minutes, put them into a twin-screw extruder for extrusion, cool them, cut them into pellets, and dry the obtained pellets for use; Step (4) Mechanical Grinding: Under the protection of nitrogen, the particles obtained in step (3) are ground into powders of 40 to 50 meshes using a grinding machine to obtain a COFs flame-retardant polyethylene composite material for rotational molding.

2. The method for preparing the COFs flame-retardant polyethylene composite material for rotational molding according to claim 1, characterized in that: In the second step, the optimal reaction temperature of the reaction mixture is 90° C. and the reaction time is 24 h.

3. The method for preparing the COFs flame-retardant polyethylene composite material for rotational molding according to claim 1, characterized in that: In the third step, the optimal stirring time is 5 h.

4. The method for preparing the COFs flame-retardant polyethylene composite material for rotational molding according to claim 1, characterized in that: In step (2), the PE wax is one of PEW-032, PEW-031, PEW-030 or a combination thereof; the linear low-density polyethylene LLDPE is one of LLDPE-7050, LLDPE-9020, LLDPE-9085 or a combination thereof; the carbon nanotube CNT is a single-walled carbon nanotube Multi-walled carbon nanotubes The toughening agent is one or a combination of POE-g-MAH, POE-g-GMA, and PE-g-MAH; the antioxidant is one or a combination of BHT, AO-1010, AO-1076, AO-3114, and AO-330.

5. The method for preparing the COFs flame-retardant polyethylene composite material for rotational molding according to claim 1, characterized in that: In step (2), the optimal blending temperature for adding the Cu@COFs-COOH powder and PE wax into the high-speed mixer is 90°C, and the blending time is 8 minutes; the optimal blending temperature for adding linear low-density polyethylene LLDPE, carbon nanotubes CNT, toughening agent, and antioxidant is 90°C, and the blending time is 4 minutes.

6. The method for preparing the COFs flame-retardant polyethylene composite material for rotational molding according to claim 1, characterized in that: In step (3), the low-density polyethylene (LDPE) is one of DFDA-7042, DFDB-7042, DFDC-7042) or a combination thereof.

7. The method for preparing the COFs flame-retardant polyethylene composite material for rotational molding according to claim 1, characterized in that: In step (3), the optimal blending temperature in the high-speed mixer is 90° C., and the blending time is 15 min.

8. A COFs flame-retardant polyethylene composite material for rotational molding, characterized in that: Specifically include the following components: Linear low-density polyethylene LLDPE 15.0%~35.0%, Low-density polyethylene LDPE 35.0%~55.0%, Flame retardant masterbatch; Wherein, the flame retardant masterbatch comprises the following components: Linear low-density polyethylene LLDPE 10.0%~35.0%, Carbon nanotubes CNT 0%~10.0%, Cu@COFs-COOH 1.0%~12.0%, Toughening agent 1.0%~10.0%, Polyethylene wax 1.0%~10.0%, Antioxidant 1.0%~10.0%; The proportions here are all in mass percentage.

Citation Information

Patent Citations

  • Flame retardant and antistatic polyethylene composition special for rotational moulding and preparation method thereof

    CN106867080A

  • High-temperature-resistant halogen-free flame-retardant automobile cable material and preparation method thereof

    CN117050415A

  • Resin film

    CN118488994A